IMPLEMENTASI PENDEKATAN RIGOROUS MATHEMATICAL THINKING (RMT) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA - Enggar Tri Aulia; Harina Fitriyani (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
The purpose of this research is to improve students' problem solving skills using Rigorous Mathematical Thinking (RMT) approach. Qualitative research method with the type of Classroom Action Research (CAR). This research was conducted in class VIII H of SMP N 2 Sewon, Bantul. As a data collection technique used consists of tests, observations, and interviews. This research data analysis technique uses an interactive analysis model according to Miles, Matthew B, Michael. Huberman (2014). The results showed that mathematics learning using rigorous mathematical thinking (RMT) approach could improve the problem solving abilities of class VIII H students of SMP N 2 Sewon.